Evaluating the Mechanical Response of Novel Synthetic Femurs Representing Osteoporotic Bone - Gluek, Cooper (My University, 2018)
Osteoporosis is a disease prevalent in older adults, characterized by increased bone porosity resulting in significant fracture risk. Orthopaedic implants are designed and validated against cadavers from the general ‘healthy’ population, but little is known about their response in osteoporotic bone. Orthopaedic implants can also be developed using synthetic bones, if they have been demonstrated to be representative of healthy bone, and offer a number of advantages. To date, no synthetic femur has been validated for the osteoporotic population. The purpose of this study was to assess novel synthetic femurs for representing this population. Custom jigs were manufactured to test two sets of ten synthetic femurs and five isolated cadaveric femurs in four-point bending, torsion, axial compression, axial failure, and screw pullout, using an Instron mechanical testing machine to record load-displacement data. Statistical significance was found in bending, torsion, and screw pullout between both synthetic sets and cadavers using one-way ANOVA with post-hoc Tukey analysis. In all instances, the synthetic femurs had lower coefficients of variation than natural specimens. Both synthetic and cadaveric femurs were CT scanned prior to testing. The data were used to measure key anatomical details and to develop a series of numerical models of the synthetic bones, using Materialize Mimics® and ABAQUS® software, evaluated using axial and bending data. The model was modified by reducing cortical thickness and modulus in an attempt to make the synthetic model better represent osteoporotic bone. Establishing synthetic femurs as suitable replacements for osteoporotic bone allows for improved orthopaedic implant development. The digital model constructed allows the synthetic to be further analyzed, improving expected response of the synthetic bones. These synthetic bones could provide a foundation for development of effective orthopaedics for this population.
Keywords: Sawbones; Finite Element Analysis; Mechanical Response; Osteoporotic; Femur